2019
DOI: 10.1029/2019jg005029
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling Changes in the Spectral Shape of Chlorophyll Fluorescence: Implications for Remote Sensing of Photosynthesis

Abstract: Novel satellite measurements of solar‐induced chlorophyll fluorescence (SIF) can improve our understanding of global photosynthesis; however, little is known about how to interpret the controls on its spectral variability. To address this, we disentangle simultaneous drivers of fluorescence spectra by coupling active and passive fluorescence measurements with photosynthesis. We show empirical and mechanistic evidence for where, why, and to what extent leaf fluorescence spectra change. Three distinct components… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
90
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(98 citation statements)
references
References 84 publications
7
90
0
1
Order By: Relevance
“…SIF has been shown to be a robust proxy for GPP (Frankenberg & Berry, ; van der Tol et al, ). While nonlinear relationships between GPP and SIF have been observed at leaf and flux‐tower scales under certain conditions, for example, strong incoming light (Magney et al, ; Verma et al, ), linear relationships have been generally observed at ecosystem and regional scales (Frankenberg et al, ; Li et al, ; Magney et al, ; Sun et al, ). The robust linear relationship at increasing scales is likely because satellite measurements are primarily measuring an integrated canopy average of low Photosynthetically Active Radiation (PAR).…”
Section: Methodsmentioning
confidence: 99%
“…SIF has been shown to be a robust proxy for GPP (Frankenberg & Berry, ; van der Tol et al, ). While nonlinear relationships between GPP and SIF have been observed at leaf and flux‐tower scales under certain conditions, for example, strong incoming light (Magney et al, ; Verma et al, ), linear relationships have been generally observed at ecosystem and regional scales (Frankenberg et al, ; Li et al, ; Magney et al, ; Sun et al, ). The robust linear relationship at increasing scales is likely because satellite measurements are primarily measuring an integrated canopy average of low Photosynthetically Active Radiation (PAR).…”
Section: Methodsmentioning
confidence: 99%
“…We also examine sensitivity to SIF reference shapes by substituting simulated estimates obtained from the SCOPE model (Van Der Tol et al, ; GOME2A‐PKv1, GOME2A‐PKexp1, and GOME2A‐PKtrop) with observed shapes obtained from leaf fluorescence spectra (Magney, Frankenberg, et al, ). Leaf‐level data account for reabsorption by chlorophyll across red and into the far‐red wavelengths, and thus reduced magnitude up to 740 nm compared to photosystem‐level emissions assumed by SCOPE (e.g., see Figure ).…”
Section: Methodsmentioning
confidence: 99%
“…Although the intersensor wavelength range is relatively small (~30 nm), absolute fluorescence values vary by more than a factor of 2 in this region (Joiner et al, ; Köhler, Guanter, et al, ; Sun et al, ). Reference SIF shapes derived from leaf‐level studies suggest that far‐red fluorescence spectra, and thus wavelength conversions, are roughly consistent across species (Magney, Frankenberg, et al, ). In principle, a look‐up table approach could be used to determine a multiplicative factor to convert between different wavelengths evaluated across sensors/retrievals based on a reference spectrum derived from an average across multiple plant species.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations